2013
DOI: 10.1177/1059840513513155
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating School Wellness Policy in Curbing Childhood Obesity in Anchorage, Alaska

Abstract: In 2006, the Anchorage School District implemented a school wellness policy to address the problem of obesity among its elementary-aged students. We assessed whether the addition of this policy is effective in protecting or preventing students from becoming overweight/obese over time. The methods involved following two cohorts of students for 5 years, a cohort not exposed and a cohort exposed to the policy. The results show that exposure to the policy does not significantly protect or prevent students from bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The lack of significant overall relationships among WellSAT scores and student weight-related outcomes in this study adds to the body of research indicating mixed results of the influence of school wellness policies on student health, especially within student BMI and physical activity. In agreement with our results, research studies from school districts in other states have found that the enactment of a school wellness policy was not significantly associated with a change in BMI [21] or prevalence of student obesity [22]. This study found no significant relationship between the overall scores of wellness policies and mean days of student physical activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of significant overall relationships among WellSAT scores and student weight-related outcomes in this study adds to the body of research indicating mixed results of the influence of school wellness policies on student health, especially within student BMI and physical activity. In agreement with our results, research studies from school districts in other states have found that the enactment of a school wellness policy was not significantly associated with a change in BMI [21] or prevalence of student obesity [22]. This study found no significant relationship between the overall scores of wellness policies and mean days of student physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…Studies evaluating the impact of school wellness policies on students' Body Mass Index (BMI) have shown mixed results; with some studies indicating decreases in student BMI and/or adolescent overweight/obesity prevalence [17][18][19][20], some showing no significant change in BMI or student obesity prevalence [21,22], and some showing a higher obesity prevalence among students in states with stronger and more comprehensive obesity prevention policies [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Strong policies governing the school environment are key influencers of the implementation of evidence-based practices in schools, and policies can facilitate the development of settings that support health-promoting behaviors among students [1][2][3][4]. Numerous policies have been developed at the federal, state, district and school level, addressing practices such as nutrition education [5][6][7][8][9][10], school lunch timing [8,9,11,12] and lunch duration [8,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…School nutrition manager activities related to involving students in planning school meal menus and seeking student input on vegetable offerings in school meals were linked to state law on strategies to increase participation in school meals;2 Conducting a taste test activity with students was linked to state law on methods to solicit input;3 Setting up a booth at a school event to advertise school meals was linked to state law on how to engage parents/community;4 Participating in a school or district meeting about the local wellness policy was linked to state law on stakeholders involved in wellness policy development; * p < 0.05, ** p < 0.01, *** p < 0.001; AOR: Adjusted odds ratio; CI: confidence interval; Ref: referent category; FRPL: free/reduced-price lunch.…”
mentioning
confidence: 99%
“…Thus, the school, along with the supporting school infrastructure, serves as a logical setting to address the childhood obesity epidemic, as well as other health disparities. Schools have an obvious opportunity to reach a large and diverse population, given the fact the children spend a majority of their day in the school setting and the potential influence that the school community can have over student health habits, such as nutritional intake and physical activity . Schools cannot fight the obesity epidemic alone; however, when children are in the custody of teachers and school administrators, there is a responsibility and opportunity to attend to students' health needs.…”
mentioning
confidence: 99%